2001
DOI: 10.1073/pnas.141002798
|View full text |Cite
|
Sign up to set email alerts
|

The type I BMP receptor BmprIB is essential for female reproductive function

Abstract: Maintenance of female reproductive competence depends on the actions of several hormones and signaling factors. Recent reports suggest roles for bone morphogenetic proteins (BMPs) in early stages of folliculogenesis. A role for the type I BMP receptor BmprIB as a regulator of ovulation rates in sheep has been described recently, but little is known about the roles of BMP signaling pathways in other aspects of reproductive function. We report here that BMPRIB is essential for multiple aspects of female fertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(123 citation statements)
references
References 45 publications
(49 reference statements)
12
110
0
1
Order By: Relevance
“…This is in accordance with the phenotype observed in Bmp15 null mice where no apparent defects in follicular development were observed; but ovulation rate was lower and the ovulated oocytes showed reduced developmental potential (Yan et al 2001, Su et al 2004. Interestingly, the Bmpr1b null mice exhibited defects in cumulus expansion which, in turn, prevented in vivo fertilization (Yi et al 2001). Moreover, recent results obtained in two different mouse studies showed that BMP15 is likely involved in cumulus expansion (Gueripel et al 2006, Yoshino et al 2006.…”
Section: Expression Of Bmps and Bmpr In Pig Folliclessupporting
confidence: 88%
“…This is in accordance with the phenotype observed in Bmp15 null mice where no apparent defects in follicular development were observed; but ovulation rate was lower and the ovulated oocytes showed reduced developmental potential (Yan et al 2001, Su et al 2004. Interestingly, the Bmpr1b null mice exhibited defects in cumulus expansion which, in turn, prevented in vivo fertilization (Yi et al 2001). Moreover, recent results obtained in two different mouse studies showed that BMP15 is likely involved in cumulus expansion (Gueripel et al 2006, Yoshino et al 2006.…”
Section: Expression Of Bmps and Bmpr In Pig Folliclessupporting
confidence: 88%
“…Bmpr1a null/+ males homozygous for bcre-32 were crossed with females of genotype Bmpr1a cl/cl . In addition, we used mice carrying a null allele of Bmpr1b (Bmpr1b null ) (Yi et al, 2001): Bmpr1a null/+ ; Bmpr1b null/+ males homozygous for bcre-32 were crossed with Bmpr1a cl/cl ; Bmpr1b null/+ females. PCR detection of wild-type, floxed and recombined Bmpr1a alleles was as described previously (Mishina et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The ALK6 knockout mouse does not display the same phenotype as the Booroola ewe [36]. ALK6 knockout mice appear to have normal ovarian follicular development and ovulation rates although there is a reduction in fertility perhaps caused by the failure of normal cumulus expansion.…”
Section: The Alk6 (Bmpr-ib) Mutationmentioning
confidence: 96%